2021
DOI: 10.1007/s10853-020-05628-w
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelastic properties and γ’-solvus temperatures of single-crystal Ni-base superalloys

Abstract: The present work shows that thermal expansion experiments can be used to measure the γʼ-solvus temperatures of four Ni-base single-crystal superalloys (SX), one with Re and three Re-free variants. In the case of CMSX-4, experimental results are in good agreement with numerical thermodynamic results obtained using ThermoCalc. For three experimental Re-free alloys, the experimental and calculated results are close. Transmission electron microscopy shows that the chemical compositions of the γ- and the γʼ-phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…From VF100 to VF0, that is, with decreasing content of the c¢ stabilizing elements, the peak temperature decreases and the thermal expansion anomaly becomes less pronounced (Figure 7(c) and Table VI). Similar thermal expansion anomalies have been reported in the literature [11,52] for a series of CMSX-4 type Ni-and Co-base superalloys. The authors demonstrated that the temperature of the thermal expansion peak coincides with the c¢ solvus temperature and suggested dilatometry as a highly sensitive probe for the determination of T c¢ .…”
Section: E Thermal Expansionsupporting
confidence: 88%
See 2 more Smart Citations
“…From VF100 to VF0, that is, with decreasing content of the c¢ stabilizing elements, the peak temperature decreases and the thermal expansion anomaly becomes less pronounced (Figure 7(c) and Table VI). Similar thermal expansion anomalies have been reported in the literature [11,52] for a series of CMSX-4 type Ni-and Co-base superalloys. The authors demonstrated that the temperature of the thermal expansion peak coincides with the c¢ solvus temperature and suggested dilatometry as a highly sensitive probe for the determination of T c¢ .…”
Section: E Thermal Expansionsupporting
confidence: 88%
“…In the alloys investigated here, the dissolution or precipitation of the c¢ phase is always associated with a significant positive contribution to the thermal expansion (Figure 7), which was also observed in other Coand Ni-based superalloys. [11,40,52] Surprisingly, such an effect, even though a weaker one, also occurs in VF0, which indicates that at low temperatures, VF0 does not have a single-phase microstructure in equilibrium. During slow heating in the dilatometer, precipitation of c¢ starts at about 700°C in VF0 samples, before the precipitates have dissolved again at the c¢ solvus temperature of 881°C.…”
Section: Anomalies Of the Thermal Expansion Behaviormentioning
confidence: 97%
See 1 more Smart Citation
“…Despite its simplicity, this model has proved an adequate descriptor of high-temperature creep performance. [26] 3.…”
Section: ½2mentioning
confidence: 99%
“…The γ′ solvus temperature is a critical parameter when evaluating the stability of Ni-based superalloys under high-temperature working environments and designing alloy heat treatment schedules [40] . ML has also been applied for predicting the γ′ solvus temperature of Ni-based superalloys [41][42][43][44] .…”
Section: Alloy Optimization and Design Of Ni-based Superalloysmentioning
confidence: 99%